Gender, Hormonal, and Comorbidity-Related Variations in Osteoarthritis: A Comparative Observational Study - Katta, Vaishnavi; Ramana, Yasaswi; Kumar, Manas; Chejarla, Navyasri; Velpula, Lavanya; Shammi, Shaik (Indian Journal of Pharmacy Practice)
Background: Osteoarthritis (OA) is the most common degenerative joint condition globally, especially in older adults. Factors like gender, hormones, BMI, affected joints, and other health issues can affect the onset and progression of OA. Objectives: This study evaluates the relationship between osteoarthritis and five factors: gender, menstrual status (menstruating vs. menopausal), Body Mass Index (BMI), affected joints, and comorbid conditions in adults. Materials and Methods: A cross-sectional study was conducted at a tertiary care hospital in Guntur, Andhra Pradesh with 60 osteoarthritis patients. Data was collected through patient interviews and clinical record reviews, focusing on gender, age, menstrual status in women, BMI, joint involvement, and comorbidities like diabetes, hypertension, and obesity. Statistical analysis was performed using the Chi-Square test in SPSS. Results: A study of 60 participants found that Osteoarthritis (OA) was more prevalent in females (63.4%) than males (36.7%), especially in postmenopausal women (76.3%). The highest incidence was in the 45 to 50 age group at 40%. Overweight individuals and those without comorbidities made up 60% of OA cases, suggesting a link between these factors and the disease. The knee joints were most affected, with a 71.6% incidence rate. However, no statistically significant differences were noted for any variables (p>0.05), likely due to the small sample size. Conclusion: Trends indicate a higher risk of Osteoarthritis (OA) in females, especially postmenopausal women and those with excess weight, but results were not statistically significant. Larger studies with longitudinal methods are needed for clearer insights.
Keywords: Osteoarthritis; Gender Differences; Menopause; Body Mass Index; Comorbidities; Joint Involvement